Odpowiedzi

2010-01-07T20:14:38+01:00
1) y=3-4x
5x + 2(3-4x) =4
5x +6- 8x =4
-3x=- 2 /-3
x= 2/3
y= 3- 4*2/3= 1/3

2) x= -9,5 -5y
-57 -30y -3y =9
-33y=66 /-33
y= -2
x=1/2
1 1 1
Najlepsza Odpowiedź!
2010-01-07T20:41:09+01:00
Przykład nr 1:
{5x=4-2y
{4x+y=3 / - 4x

5x = 4 - 2y
y = 3 - 4x

5x = 4 - 2(3 - 4x)
5x = 4 - 6 + 8x / - 8x
- 3x = - 2 / :(-3)
x = 2/3

5 * 2/3 = 4 - 2y
3 1/3 = 4 - 2y / - 4
- 2/3 = - 2y / : (-2)
y = 1/3


y = 1/3
x= 2/3







przykład nr 2:
{6x-3y=9
{x+5y=-9,5 / - 5y

6x - 3y = 9
x = - 9,5 - 5y


6( - 9,5 - 5y) - 3y = 9
- 57 - 30 y - 3 y = 9 / + 57
- 33y = 66 / : (- 33)
y = -2


6x + 6 = 9 / - 6
6x = 3 / : 6
x = 1/2

x = 1/2
y = - 2